Newer approaches in the treatment of asthma - Patel, Kamlesh P.; Joshi, Harsh M.; Patel, Varsha J. (International Journal of Basic & Clinical Pharmacology, 2017)
Asthma is a worldwide public health problem. The most effective anti-asthmatic drugs - inhaled β2-agonists and glucocorticoids controls asthma in about 90-95% of patients. However, severe glucocorticoid-dependent and resistant asthma presents a great clinical burden. Therefore, reducing glucocorticoids - related adverse effects using novel steroid-sparing agents is needed. Furthermore, the mechanisms involved in the persistence of inflammation are poorly understood and the reasons why some patients have severe life threatening asthma and others have very mild disease are still unknown. Although glucocorticoids effectively control the inflammatory process in asthma, they have little effect on the lower airway remodeling processes that appear to play a role in the pathophysiology of asthma. Several new drugs developed to target specific components of the inflammatory process in asthma [e.g. anti-IgE antibodies (omalizumab), cytokines and/or chemokines antagonists, immunomodulators, antagonists of adhesion molecules)], have not yet been proven to be particularly effective. Hence, considering the central role of T lymphocytes in the pathogenesis of asthma, drugs targeting disease-inducing Th2 cells are promising future therapeutic strategies. Some of these new anti-asthmatic treatment approaches may in the future not only control symptoms and modify the natural course of asthma, but also potentially prevent or cure the disease. Hence, the development of novel drugs may allow resolution of these changes.